Charlie Hebdo, 2015: 'Liveness' and acceleration of conflict in a hybrid media event. (June 2019) - Sumiala, Johanna; Tikka, Minttu; Valaskivi, Katja
In this article, the authors examine the intensification of liveness and its effects in the Charlie Hebdo attacks that took place in Paris in January 2015. In their investigation they first re-visit the existing theoretical literature on media, event and time, and discuss in particular the relationship between media events and the idea of liveness. They then move on to the empirical analysis of the Charlie Hebdo attacks and demonstrate the aspects of intensified liveness in the circulation of selected tweets. The analysis is based on a multi-method approach developed for the empirical study of hybrid media events. In conclusion, the authors argue that the liveness, experienced and carried out simultaneously on multiple platforms, favours stereotypical and immediate interpretations when it comes to making sense of the incidents unfolding before the eyes of global audiences. In this condition, incidents are interpreted 'en direct', but within the framework of older mnemonic schemes and mythologization of certain positions (e.g. victims, villains, heroes) in the narrative. This condition, they claim, further accelerates the conflict between the different participants that took part in the event.